SteE regulation of Th1/Th2 cytokines expression in chickens during S. Pullorum infection - Zh. Liu; A. Fotin; R. Petrov; J. Ma; T. Fotina (Ukrainian Journal of Veterinary Sciences, 2023)
Nowadays, timely monitoring of zoonotic agents, including salmonellosis, which are caused by various serovars of the family Salmonella, is relevant. Attention should be paid to the study of cytokine levels in combination with immunological studies. This helps clarify the pathogenesis of infectious diseases and develop preventive measures. The main purpose of study was to detect the process of regulating Th1/Th2 cytokines expression in chickens infected with salmonellosis. The field strain of S. Pullorum CVCC 530 was used in the research. The steE deletion mutant (ΔsteE) and steE-complemented ΔsteE:steE (ΔsteE+steE) strains were constructed in the WT strain using the λ-Red recombination method. Chickens were orally infected with WT, ΔsteE, and ΔsteE+steE strains (1×109 CFU/individual). The effect of steE on the host immune response remains unknown. Compared with the group infected with the WT or ΔsteE+steE strain, IL-12 and IFN-γ mRNA transcript levels were significantly higher, while IL-10 mRNA expression was significantly reduced in the liver and bursa infected with the ΔsteE strain; IL-4 showed a dramatically reduced transcription level, but IL-18 mRNA expression was significantly increased in the ΔsteE strain – spleen, cecum, and heart; IL-10 mRNA expression was significantly reduced in the spleen and cecum infected with the ΔsteE strain. These results suggest that steE may regulate the Th1/Th2 cytokine response balance in chickens infected with S. Pullorum and provide new insights into the pathogenesis of salmonellosis for the treatment of persistent infection